Measuring the impact of ChatGPT in enhancing number sense acquisition: A mixed-method study - Kadir; Gita Fajrin Jafar; Benjamin B. Mangila (Jurnal Elemen, 2025)
The effectiveness of ChatGPT in enhancing mathematics learning outcomes for students remains a topic of debate despite its growing application in educational settings. This study seeks to assess the impact of ChatGPT on students' understanding of number concepts in mathematics, particularly for 7th-grade junior high school students, by employing a combination of classroom experiments and a control group while gathering students' perspectives on its use. In a mixed-method approach, the quantitative findings indicate that ChatGPT usage does not significantly improve students' academic performance in number concepts. However, qualitative insights from the classroom experiments reveal that students perceived several benefits, such as increased efficiency in studying, better comprehension of number-related problems, enhanced accuracy in solving problems, and assistance in overcoming learning challenges. While ChatGPT did not directly affect academic outcomes, it was found to be a valuable supplementary tool in the learning process. Based on these findings, this study recommends that educators consider incorporating ChatGPT to complement traditional teaching methods to enhance the overall learning experience of number concepts.